SUPERVISI GURU MATA PELAJARAN DI SDN 2 BAHITOM KABUPATEN MURUNG RAYA - TRISNUARI, TRISNUARI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The purpose of this literature study is to find out and study the principles and objectives of educational supervision. The method in this research is literature study, namely looking for literature that is relevant to the topic raised and describing it to compare each literature. The results of this research show that the principles in educational supervision must be to guide teachers in carrying out teaching and supervising, easy to implement, not urgent, working together to advance education, always expecting change for the better. The targets in educational supervision are academic targets which include supervision of the academic or learning process that occurs at school so that it improves and is of better quality. Administrative targets include the administrative completeness of school principals and teachers such as the availability of facilities, textbooks, teaching tools such as learning implementation plans (RPP), annual programs, semester programs, effective time analysis and KKM. Teacher learning tools must always be updated and adapted to the latest curriculum. The target of the Institution is supervision of schools to improve the quality of the institution in general and improve the quality of schools. The target of this institution is related to school accreditation, completeness of documents and school activities which must be properly documented so that when the institution is supervised, the required documents are available and updated. Schools must also have a strategic plan for future planning, so that the institution can develop. ABSTRAKTujuan dari studi literatur ini adalah untuk mengetahui dan mempelajari prinsip dan sasaran dari supervisi Pendidikan. Metode dalam penelitian ini adalah studi literatur yaitu mencari literatur yang relevan dengan topik yang diangkat serta mendeskripsikannya untuk membandingkan masing-masing literatur. Hasil dari penelitian ini menunjukkan bahwa prinsip dalam supervisi pendidikan yang harus yaitu membimbing guru dalam melaksanakan pengajaran dan mengawasi, mudah dilaksanakan, tidak mendesak, bekerjasama dalam memajukan pendidikan, selalu mengharapkan perubahan ke arah yang lebih baik. Sasaran dalam supervisi Pendidikan yaitu sasaran akademik yang meliputi pengawasan terhadap proses akademi atau pembelajaran yang terjadi di sekolah agar lebih meningkat dan berkualitas. Sasaran administrasi yang meliputi kelengkapan administrasi kepala sekolah dan guru seperti ketersediaan sarana, buku-buku pelajaran, perangkat mengajar seperti rencana pelaksanaan pembelajaran (RPP), program tahunan, program semester, analisis waktu efektif dan KKM. Perangkat pembelajaran guru harus selalu diperbaharui dan disesuaikan dengan kurikulum terbaru. Sasaran Lembaga merupakan pengawasan terhadap sekolah untuk meningkatkan kualitas lembaga secara umum dan meningkatkan kualitas sekolah. Sasaran Lembaga ini terkait dengan akreditasi sekolah, kelengkapan-kelengkapan dokumen dan kegiatan sekolah yang harus didokumentasikan dengan baik agar pada saat lembaga disupervisi, dokumen yang diperlukan sudah tersedia dan diperbaharui. Sekolah juga harus mempunya rencana strategi untuk perencanaan ke depan, agar lembaga dapat berkembang.